2016
DOI: 10.1590/0103-8478cr20151612
|View full text |Cite
|
Sign up to set email alerts
|

Control of the lipid oxidation in Nile tilapia feed

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The tubes were heated in boiling water bath (100 °C) for 40 min and cooled in running water for 10 min. The TBARS were measured at 538 nm and the values were expressed as mg malonaldehyde/kg (GRASSI et al, 2016(GRASSI et al, , 2018.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tubes were heated in boiling water bath (100 °C) for 40 min and cooled in running water for 10 min. The TBARS were measured at 538 nm and the values were expressed as mg malonaldehyde/kg (GRASSI et al, 2016(GRASSI et al, , 2018.…”
mentioning
confidence: 99%
“…1.B) biomasses in the rations are enough to provide the lowest TBARS in the diets. GRASSI et al (2016) also reported a delay in tilapia diets stored until 12 months when a bacterial biomass (Rubrivivax gelatinosus) was added up to 0.14% and assigned the effect to the presence of carotenoids in the biomass.…”
mentioning
confidence: 99%